How do you condense 4[lnz+ln(z+5)−2ln(z−5)]?
Answers
Answered by
0
Solution:
/* i) n ln a = ln aⁿ
ii)ln m + ln n = ln (mn)
iii) ln m - ln n = ln (m/n) */
Now ,
4[lnz+ln(z+5)−2ln(z−5)]
= 4[lnz+ln(z+5)−ln(z−5)²]
= 4[lnz(z+5)−ln(z−5)²]
=4[ln{z(z+5)/(z-5)²}]
= [ln{z(z+5)/(z-5)²}]⁴
••••
/* i) n ln a = ln aⁿ
ii)ln m + ln n = ln (mn)
iii) ln m - ln n = ln (m/n) */
Now ,
4[lnz+ln(z+5)−2ln(z−5)]
= 4[lnz+ln(z+5)−ln(z−5)²]
= 4[lnz(z+5)−ln(z−5)²]
=4[ln{z(z+5)/(z-5)²}]
= [ln{z(z+5)/(z-5)²}]⁴
••••
Similar questions